Hypolithic Photosynthesis in Hydrothermal Areas and Implications for Cryptic Oxygen Oases on Archean Continental Surfaces - Havig, Jeff R.; Hamilton, Trinity L. (Frontiers in Earth Science, 2019)
Mounting geochemical evidence suggests microorganisms capable of oxygenic photosynthesis (e.g., Cyanobacteria) colonized Archean continental surfaces, driving oxidative weathering of detrital pyrites prior to the 2.5 Ga Great Oxidation Event (e.g., Stüeken et al., 2012; Reinhard et al., 2013; Lalonde and Konhauser, 2015; Havig et al., 2017a). Modern terrestrial environments dominated by biofilms comprised of phototrophs include hydrothermal systems (e.g., Yellowstone National Park) and hypolithic communities found in arid to hyper-arid deserts (e.g., McMurdo Dry Valleys of Antarctica, Atacama Desert of Chile). Here, we explore phototrophic communities in both hypolithic and hot spring environments in Yellowstone National Park as potential analogs to Archean continental surfaces. Hypolithic communities in geothermal settings were similar in both composition and carbon uptake rates to proximal hot spring communities. It is our opinion that hydrothermal area hypolithic communities represent modern analogs of communities that colonized Archean continental surfaces, producing oxygen locally, and facilitating microbially-mediated pyrite oxidation prior to the presence of free oxygen in the global atmosphere.